Membrane electrode assembly

By uniformly distributing particles with the function of decomposing hydrogen peroxide on the moving side of the membrane electrode assembly, the degradation problem caused by radiation in the solid polymer electrolyte is solved, and the chemical durability of the electrolyte membrane is significantly improved.

JP7648322B2Active Publication Date: 2025-03-18KK TOYOTA CHUO KENKYUSHO +1
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
JP2021073385
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-04-23
Publication Date
2025-03-18
Estimated Expiration
2041-04-23

AI Technical Summary

Technical Problem

The prior art is difficult to effectively suppress the radiation generated in solid polymer electrolytes, resulting in degradation of the electrolyte membrane and shortening the lifetime.

Method used

The first particles are evenly distributed on the moving side of the membrane electrode assembly, made of a first compound having the function of decomposing hydrogen peroxide.

Benefits of technology

By distributing these particles on the moving electrode side, it is possible to prevent the hydrogen peroxide generated on the moving electrode side from being decomposed into water and oxygen, thereby improving the chemical durability of the electrolyte membrane.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007648322000003
    Figure 0007648322000003
  • Figure 0007648322000004
    Figure 0007648322000004
  • Figure 0007648322000005
    Figure 0007648322000005
Patent Text Reader

Abstract

To provide a membrane electrode assembly capable of suppressing the generation of radicals causing a deterioration in a solid polymer electrolyte.SOLUTION: A membrane electrode assembly includes an electrolyte membrane including a solid polymer electrolyte, an anode catalyst layer bonded to one side of the electrolyte membrane, a cathode catalyst layer bonded to the other side of the electrolyte membrane, and a first fine particle segregating on an anode side in the electrolyte membrane, the first fine particle comprising a first compound having a function to decompose hydrogen peroxide. The first compound is preferably tungsten oxide (+IV, +V, +VI) and / or tungstate.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a membrane electrode assembly, and more particularly to a membrane electrode assembly containing an additive that has a function of suppressing the generation of radicals that cause deterioration of a solid polymer electrolyte. [Background technology]

[0002] Membrane electrode assemblies (MEAs) are used in the areas where electrochemical reactions occur in soda electrolysis devices, water electrolysis devices, fuel cells, etc. It is said that MEAs are deteriorated when the electrolyte is attacked by radicals generated directly by the direct reaction of oxygen and hydrogen, or by electrochemical reactions, or by radicals generated via hydrogen peroxide. For example, in fuel cells, radical attack is known to increase the resistance of the electrolyte membrane, increase cross leakage, and shorten the lifespan due to thinning. Furthermore, degradation products generated by radical attack may cause catalyst poisoning, which may result in a decrease in electrolytic performance and cell performance.

[0003] In order to solve this problem, various proposals have been made in the past. For example, Patent Document 1 discloses a solid polymer electrolyte membrane in which a second layer containing an ion exchange material and platinum-supported carbon is formed on one side of a composite membrane in which an expanded PTFE membrane is impregnated with an ion exchange material. The document describes that dispersing platinum-supported carbon in a high-strength solid polymer electrolyte improves the life of a fuel cell.

[0004] Patent Document 2 discloses a polymer electrolyte membrane comprising a membrane-like base material made of a polymer electrolyte and precious metal particles dispersed in the base material, in which the precious metal particles are dispersed with a concentration gradient in the thickness direction of the base material. The same document states: (A) By dispersing noble metal particles in the film, radicals can be deactivated. (B) The noble metal particles can deactivate radicals more efficiently when they are unevenly distributed on the cathode side rather than uniformly dispersed in the membrane; and (C) The maximum concentration of the noble metal particles is preferably located near the surface of the polymer electrolyte membrane that is in contact with the cathode catalyst layer. is stated.

[0005] In Patent Document 3, (a) applying a degradation inhibitor solution containing a sulfur-containing aromatic compound to one surface of a substrate made of a hydrocarbon electrolyte, and removing the solvent to form an degradation inhibitor layer on one surface of the substrate; (b) forming a cathode catalyst layer on the surface of the substrate that has the deterioration prevention layer, and forming an anode catalyst layer on the surface of the substrate that does not have the deterioration prevention layer; The resulting membrane electrode assembly is disclosed. The same document states: (A) The sulfur-containing aromatic compound has a function as an anti-degradation agent that deactivates radicals and a function of suppressing the deposition of platinum in the catalyst layer in the electrolyte membrane, and (B) The MEA with the degradation prevention layer exhibits less degradation of the polymer electrolyte membrane than the MEA without the degradation prevention layer. is stated.

[0006] Furthermore, Patent Document 4 discloses an electrolyte membrane for a fuel cell in which an oxygen scavenger containing a metal with a strong affinity for oxygen, such as Ti, is unevenly distributed on the cathode side using a sol-gel method. The same document states: (A) By disposing an oxygen scavenger on the cathode side of the electrolyte membrane, cross-leak of oxygen from the cathode side to the anode side can be suppressed, and (B) This suppresses the formation of hydrogen peroxide, which causes degradation of the electrolyte membrane, improving the durability of the electrolyte membrane. is stated.

[0007] Patent Documents 1 to 4 describe that the durability of an electrolyte membrane can be improved by adding a certain type of additive to the electrolyte membrane, and Patent Documents 2 and 3 describe that the degradation suppression effect is high when this type of additive is unevenly distributed on the cathode side.

[0008] Among these additives, noble metal particles (Patent Documents 1 and 2) have the effect of decomposing hydroxyl radicals. However, since Fe ions, which are the cause of hydroxyl radical generation, are randomly present in the thickness direction of the electrolyte membrane, the positions at which hydroxyl radicals are generated are also random. Therefore, even if noble metal particles are unevenly distributed on the cathode side, there is a problem that hydroxyl radicals cannot be efficiently decomposed. In addition, since the sulfur-containing aromatic compound (Patent Document 3) is an organic substance, there is a problem that it is easily decomposed by hydroxyl radicals and loses its effect, and there is also a problem that the sulfur-containing aromatic compound poisons the catalyst when it moves to the catalyst layer. Furthermore, the method described in Patent Document 4 involves a sol-gel reaction of a metal alkoxide in an electrolyte membrane to produce a metal oxide, which is then reduced to produce an oxygen scavenger, and thus has the problem of being a complicated production method. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] JP 2014-139939 A [Patent Document 2] JP 2012-164647 A [Patent Document 3] JP 2013-175421 A [Patent Document 4] JP 2007-042491 A Summary of the Invention [Problem to be solved by the invention]

[0010] An object of the present invention is to provide a membrane electrode assembly capable of suppressing the generation of radicals that cause deterioration of a solid polymer electrolyte. [Means for solving the problem]

[0011] In order to solve the above problems, the membrane electrode assembly according to the present invention comprises: an electrolyte membrane including a solid polymer electrolyte; an anode catalyst layer bonded to one surface of the electrolyte membrane; a cathode catalyst layer bonded to the other surface of the electrolyte membrane; First fine particles segregated on the anode side in the electrolyte membrane; Equipped with The first fine particles are made of a first compound having a function of decomposing hydrogen peroxide. Effect of the Invention

[0012] Deterioration of the electrolyte membrane is (a) Oxygen that has permeated from the cathode to the anode reacts with hydrogen on the anode catalyst to produce H2O2, (b) H2O2 produced on the anode catalyst diffuses into the electrolyte membrane, where it reacts with Fe, an impurity in the electrolyte membrane, to produce hydroxyl radicals. (c) Hydroxyl radicals decompose electrolytes. This is thought to be caused by the

[0013] Therefore, if the first fine particles having the function of decomposing hydrogen peroxide are unevenly distributed on the anode side, H2O2 generated at the anode is decomposed into water and oxygen before it becomes hydroxyl radicals. As a result, the decomposition of the electrolyte membrane is suppressed, and the chemical durability of the electrolyte membrane is improved. [Brief description of the drawings]

[0014] [Figure 1] Fig. 1(A) is an SEM image of the petri dish side surface of the electrolyte membrane obtained in Example 5. Fig. 1(B) is an SEM image of the air side surface of the electrolyte membrane obtained in Example 5. [Diagram 2] 1 shows the cumulative amount of F ion elution after 90 hours from the electrolyte membranes obtained in Examples 1 to 7 and Comparative Examples 1 and 2. [Diagram 3] 1 shows the cumulative amount of F ion elution after 90 hours from the electrolyte membranes obtained in Examples 2 and 5 and Comparative Examples 3 and 4. [Figure 4] 4 shows the IV performance of the fuel cells obtained in Example 2 and Comparative Example 2. [Diagram 5] H2O2 decomposition rate of various additives. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] An embodiment of the present invention will be described in detail below. [1. Membrane electrode assembly] The membrane electrode assembly according to the present invention comprises: an electrolyte membrane including a solid polymer electrolyte; an anode catalyst layer bonded to one surface of the electrolyte membrane; a cathode catalyst layer bonded to the other surface of the electrolyte membrane; First fine particles segregated on the anode side in the electrolyte membrane; It is equipped with:

[0016] The membrane electrode assembly is (a) ions of a second metal element having a radical scavenging function, which are ion-exchanged with the acid groups of the solid polymer electrolyte, and / or (b) second fine particles made of a second compound containing the second metal element, the second fine particles being dispersed in the electrolyte membrane; It may further include.

[0017] [1.1. Electrolyte membrane] The electrolyte membrane contains a solid polymer electrolyte. In the present invention, the type of the solid polymer electrolyte contained in the electrolyte membrane is not particularly limited. The solid polymer electrolyte may be either a fluorine-based electrolyte or a hydrocarbon-based electrolyte. The electrolyte membrane may contain any one of these solid polymer electrolytes, or may contain two or more of them. The type of acid group in the solid polymer electrolyte is not particularly limited. Examples of the acid group include a sulfonic acid group, a carboxylic acid group, a phosphonic acid group, and a sulfonimide group. The solid polymer electrolyte may contain only one of these acid groups, or may contain two or more of them.

[0018] Examples of fluorine-based electrolytes include Nafion (registered trademark), Flemion (registered trademark), Aquivion (registered trademark), and Aciplex (registered trademark). The fluorine-based electrolyte includes not only fully fluorinated electrolytes that do not contain C—H bonds in the polymer structure, but also partially fluorinated electrolytes that contain C—H bonds and C—F bonds in the polymer structure.

[0019] Examples of the hydrocarbon electrolyte include: (a) A wholly aromatic hydrocarbon-based electrolyte comprising polyether ether ketone, polysulfone, polyether sulfone, polyimide, polyphenylene, polyamide, polyamide imide, or a derivative thereof, into which an acid group such as a sulfonic acid group has been introduced; (b) partially aromatic hydrocarbon electrolytes having an aromatic ring in a part of the polymer chain of an aliphatic hydrocarbon electrolyte; etc.

[0020] Furthermore, the electrolyte membrane may be made of only a solid polymer electrolyte (composite electrolyte) containing various additives, or may be a composite of a composite electrolyte and a reinforcing material. In this case, the type of the reinforcing material is not particularly limited. Examples of reinforcing materials include: (a) Porous membranes and nonwoven fabrics of fluororesins such as polytetrafluoroethylene (PTFE), perfluoroalkoxyalkane (PFA), perfluoroethylenepropene copolymer (FEP), and ethylenetetrafluoroethylene copolymer (ETFE); (b) Porous membranes and nonwoven fabrics of hydrocarbon resins such as polyethylene (PE) and polypropylene (PP), etc.

[0021] [1.2. Anode catalyst layer] An anode catalyst layer is bonded to one side of the electrolyte membrane. The anode catalyst layer includes an electrode catalyst (anode catalyst) active in hydrogen oxidation reaction and a catalyst layer ionomer. The anode catalyst may be composed of only catalyst particles (A) active in hydrogen oxidation reaction, or the catalyst particles (A) may be supported on the surface of a carrier. In the present invention, the materials of the catalyst layer ionomer, the catalyst particles (A), and the carrier are not particularly limited, and the most suitable materials can be selected depending on the purpose.

[0022] The catalyst layer ionomer on the anode side may be made of the same material as the solid polymer electrolyte constituting the electrolyte membrane, or may be made of a different material. The catalyst particles (A) include, for example, precious metals, alloys containing two or more precious metals, and alloys of one or more precious metals and one or more base metals. Examples of the carrier include carbon black, carbon nanotubes, carbon nanohorns, activated carbon, natural graphite, mesocarbon microbeads, and glassy carbon powder.

[0023] [1.3. Cathode catalyst layer] A cathode catalyst layer is bonded to the other surface of the electrolyte membrane. The cathode catalyst layer includes an electrode catalyst (cathode catalyst) active in the oxygen reduction reaction and a catalyst layer ionomer. The cathode catalyst may be composed only of catalyst particles (B) active in the oxygen reduction reaction, or the catalyst particles (B) may be supported on the surface of a carrier. In the present invention, the materials of the catalyst layer ionomer, the catalyst particles (B), and the carrier are not particularly limited, and the most suitable materials can be selected depending on the purpose.

[0024] The catalyst layer ionomer on the cathode side may be made of the same material as the solid polymer electrolyte constituting the electrolyte membrane, or may be made of a different material. Examples of the catalyst particles (B) include precious metals, alloys containing two or more precious metals, and alloys containing one or more precious metals and one or more base metals. Examples of the carrier include carbon black, carbon nanotubes, carbon nanohorns, activated carbon, natural graphite, mesocarbon microbeads, and glassy carbon powder.

[0025] [1.4. First fine particle] [1.4.1. Materials] The "first fine particles" refer to fine particles made of a first compound (inorganic compound) having the function of decomposing hydrogen peroxide. The type of the first compound is not particularly limited as long as it has the function of decomposing hydrogen peroxide. Examples of the first compound include a tungsten compound, a ruthenium compound, a tin compound, and a molybdenum compound. Among these, the first compound is preferably a tungsten compound, which has a higher hydrogen peroxide decomposition ability than other materials and is therefore suitable as a material for the first fine particles.

[0026] Examples of tungsten compounds include: (a) Tungsten oxide (+IV, +V, +VI), (b) Tungstate etc. The first fine particles may be made of any one of these, or may be a mixture containing two or more of them.

[0027] Tungsten oxide may be anhydrous or hydrated. Tungsten oxide is particularly preferably WO3·(1 / 3)H2O or WO3·2H2O. WO3 1 / 3 hydrate or dihydrate has a significantly higher hydrogen peroxide decomposition ability than other tungsten oxides, and is therefore particularly suitable as a material for the first microparticles. Examples of tungstates include Al2(WO4)3, BaWO4, FeWO4, Ni2WO4, Cu2WO4, and ZnWO4.

[0028] [1.4.2. Position of the first particle] The first fine particles are segregated on the anode side in the electrolyte membrane, which is different from the conventional method. Here, "distributed unevenly on the anode side" means that the content of the first fine particles contained in the anode side region is greater than the content of the first fine particles contained in the cathode side region. The "anode side region" refers to the region from the anode side surface of the electrolyte membrane to the center of the electrolyte membrane. The "cathode side region" refers to the region from the center of the electrolyte membrane to the cathode side surface of the electrolyte membrane.

[0029] Hydrogen peroxide is generated when oxygen that has permeated from the cathode to the anode reacts with hydrogen on the anode catalyst. In order for hydrogen peroxide generated on the anode catalyst to be decomposed into water and oxygen before it becomes radicals, the closer the position of the first fine particles is to the anode side, the better. In order to suppress deterioration due to radicals, the first fine particles are preferably located directly under the anode side surface of the electrolyte membrane.

[0030] [1.4.3. Average content of first fine particles] The "average content" refers to the ratio of the mass of the first fine particles to the total mass of the solid polymer electrolyte and the first fine particles contained in the anode side region or the cathode side region.

[0031] The average content of the first fine particles in the anode side region affects the durability of the membrane electrode assembly. The higher the average content of the first fine particles in the anode side region, the more the durability of the membrane electrode assembly improves. To obtain such an effect, the average content of the first fine particles in the anode side region is preferably 0.1 mass% or more.

[0032] On the other hand, if the average content of the first fine particles in the anode side region is excessive, the mechanical strength may decrease and the membrane may crack. Alternatively, aggregates of the first fine particles may penetrate the membrane and become the starting point of gas leakage. Therefore, the average content of the first fine particles in the anode side region is preferably 5.0 mass% or less.

[0033] On the other hand, hydrogen peroxide generated on the anode catalyst may diffuse through the electrolyte membrane and reach the cathode side. However, if the electrolyte membrane contains impurities that are active in the Fenton reaction, the hydrogen peroxide will decompose into radicals before reaching the cathode. Therefore, adding the first fine particles to the cathode side region is not very useful. Therefore, the average content of the first fine particles in the cathode side region is preferably less than 0.1 mass%.

[0034] [1.4.4. Average particle size of first fine particles] The term "average particle size of the first fine particles" refers to the average value of the maximum dimension of 200 or more first fine particles randomly selected under microscope observation.

[0035] The average particle size of the first fine particles is not particularly limited, and an optimal average particle size can be selected according to the purpose. In general, if the average particle size of the first fine particles is too small, the first fine particles may aggregate and have a small surface area, which may make it difficult to efficiently decompose hydrogen peroxide. Therefore, the average particle size of the first fine particles is preferably 1 nm or more. The average particle size is more preferably 5 nm or more, and more preferably 8 nm or more. On the other hand, if the average particle size of the first fine particles is too large, the mechanical strength may decrease and the film may crack. Also, if the first fine particles are arranged so as to penetrate the film, gas leakage may occur. Therefore, the average particle size of the first fine particles is preferably 500 nm or less. The average particle size is more preferably 300 nm or less, and even more preferably 65 nm or less.

[0036] [1.5. Ions of second metal element and / or second fine particles] [1.5.1. Materials] The "second metal element" refers to a metal element having a function of scavenging radicals. The term "second compound" refers to a compound containing a second metallic element. The "second fine particles" refer to fine particles made of a second compound.

[0037] Compounds and ions containing certain metal elements mainly have the effect of scavenging radicals, and therefore, by adding an appropriate amount of fine particles of compounds containing such metal elements and / or ions of such metal elements to the electrolyte membrane, deterioration of the electrolyte membrane can be further suppressed.

[0038] Examples of the second metal element include Ce, Ag, Cs, Sn, Mn, Ti, Co, Ni, Zn, Zr, Ru, Rh, Pd, Pt, Pr, etc. The electrolyte membrane may contain any one of these elements, or may contain two or more of them. Among these, the second metal element is preferably at least one element selected from the group consisting of Ce, Ag, Cs, Sn, and Mn. The second metal element is particularly preferably Ce, because these elements have a large effect of suppressing the generation of radicals or scavenging radicals.

[0039] The second compound may be a water-soluble compound or a poorly soluble compound. When a water-soluble second compound is used, the second compound dissociates in the electrolyte membrane, and some of the protons of the acid groups of the solid polymer electrolyte are replaced with ions of the second metal element. On the other hand, when a poorly soluble second compound is used, the second compound is dispersed in the electrolyte membrane. The second compound may be, for example, a nitrate, sulfate, carbonate, formate, acetate, citrate, perchlorate, phosphate, chloride, fluoride, hydroxide, or acetylacetonate compound.

[0040] [1.5.2. Content] When the electrolyte membrane contains ions of the second metal element and / or second fine particles, it is preferable that the electrolyte membrane satisfies the following formula (1). 0.0005≦M / A≦0.15 …(1) however, M / A is the ratio of the number of moles (M) of the second metal element to the number of moles (A) of acid groups contained in the solid polymer electrolyte.

[0041] Even when only the first fine particles are added to the electrolyte membrane, the deterioration of the electrolyte membrane can be effectively suppressed. However, when the ions of the second metal element and / or the second fine particles are further added in addition to the first fine particles, the deterioration of the electrolyte membrane is further suppressed due to the synergistic effect of these. To obtain such an effect, the M / A ratio is preferably 0.0005 or more. The M / A ratio is preferably 0.001 or more, more preferably 0.005 or more.

[0042] On the other hand, if the M / A ratio is too large, the conductivity of the electrolyte membrane may decrease. Therefore, the M / A ratio must be 0.15 or less. The M / A ratio is preferably 0.10 or less, more preferably 0.05 or less, more preferably 0.04 or less, and even more preferably 0.03 or less.

[0043] [1.5.3. Average particle size] When the second fine particles are added to the electrolyte membrane, the average particle size of the second fine particles is not particularly limited, and the most suitable average particle size can be selected according to the purpose. Other points regarding the average particle size of the second fine particles are the same as those of the first fine particles, so the explanation is omitted.

[0044] [1.5.4. Location of the second metallic element ion or second particle] The position where the ions of the second metal element or the second fine particles are added is not particularly limited. Since radicals are not necessarily generated in the anode side region, the ions of the second metal element and the second fine particles may be added to the cathode side region.

[0045] [2. Manufacturing method of membrane electrode assembly] The membrane electrode assembly according to the present invention comprises: (a) preparing an electrolyte membrane in which first fine particles are unevenly distributed on the anode side; (b) An anode catalyst layer and a cathode catalyst layer are bonded to both sides of the electrolyte membrane, respectively. It can be produced by the above method.

[0046] The electrolyte membrane in which the first fine particles are unevenly distributed on the anode side can be produced by various methods. For example, an electrolyte membrane containing the first particles can be obtained by dissolving or dispersing a solid polymer electrolyte and the first particles in a solvent, casting the dispersion onto a substrate surface, and removing the solvent. In this case, if the composition of the dispersion and the drying conditions are optimized, the first particles will settle before the drying is completed. As a result, an electrolyte membrane in which the first particles are unevenly distributed on the substrate side can be obtained. Alternatively, by laminating a membrane consisting of only a solid polymer electrolyte with a composite membrane containing a solid polymer electrolyte and first fine particles, and then pressing the laminate, an electrolyte membrane having the first fine particles unevenly distributed on one surface is obtained.

[0047] Examples of a method for adding ions of the second metal element or second fine particles to the electrolyte membrane include: (a) A method of adding second fine particles or a solvent-soluble compound containing a second metal element to a casting solution for producing an electrolyte membrane; (b) A method in which after preparing an electrolyte membrane, a solution containing ions of a second metal element is applied to the surface of the electrolyte membrane, and the ions of the second metal element are diffused into the electrolyte membrane; (c) a method in which after preparing an electrolyte membrane, a solution containing ions of a second metal element is applied to a surface of the electrolyte membrane, the ions of the second metal element are diffused into the electrolyte membrane, and a second compound is precipitated in the electrolyte membrane; etc.

[0048] Furthermore, as a method for forming a catalyst layer on the surface of the electrolyte membrane containing the first fine particles, for example, (a) A method of forming a catalyst layer on a substrate surface and transferring the catalyst layer to a surface of an electrolyte membrane; (b) A method of applying a paste for forming a catalyst layer on the surface of an electrolyte membrane and drying the paste; etc.

[0049] [3. Effect] Deterioration of the electrolyte membrane is (a) Oxygen that has permeated from the cathode to the anode reacts with hydrogen on the anode catalyst to produce H2O2, (b) H2O2 produced on the anode catalyst diffuses into the electrolyte membrane, where it reacts with Fe, an impurity in the electrolyte membrane, to produce hydroxyl radicals. (c) Hydroxyl radicals decompose electrolytes. This is thought to be caused by the

[0050] Therefore, if the first fine particles having the function of decomposing hydrogen peroxide are unevenly distributed on the anode side, H2O2 generated at the anode is decomposed into water and oxygen before it becomes hydroxyl radicals. As a result, the decomposition of the electrolyte membrane is suppressed, and the chemical durability of the electrolyte membrane is improved. In particular, tungsten oxide and tungstate do not dissolve in the fuel cell environment (acidity, potential) and can exist in the electrolyte membrane in the form of fine particles. Therefore, dissolved ions do not exchange with sulfonic acid groups in the electrolyte, and high proton conductivity can be maintained, so that the cell performance is less likely to deteriorate. Furthermore, among tungsten oxides, WO3·(1 / 3)H2O and WO3·2H2O have a remarkably high ability to decompose hydrogen peroxide compared to other materials, and therefore, by distributing them on the anode side of the electrolyte membrane, the chemical durability of the electrolyte membrane is improved.

[0051] Furthermore, when ions of a second metal element and / or second fine particles are further added to the electrolyte membrane in addition to the first fine particles, high durability can be obtained even if the amount of these added is relatively small. (a) The first fine particles have the effect of decomposing hydrogen peroxide to render it harmless, and even if the amount added is small, they exhibit a high hydrogen peroxide decomposition effect. (b) The second fine particles and the ions of the second metal element have the effect of scavenging radicals, (c) When the first fine particles are coexisted with the second fine particles and / or ions of the second metal element, the hydrogen peroxide decomposition effect of the first fine particles is improved, and / or (d) Even if radicals are generated from hydrogen peroxide that is not decomposed by the first fine particles, the second fine particles and / or ions of the second metal element effectively eliminate the radicals, It is thought that. EXAMPLES

[0052] (Examples 1 to 7, Comparative Examples 1 to 4) [1. Sample preparation] [1.1. Preparation of composite membrane] 1.1.1. Example 7 7.48 g of 1-propanol was added to 9.42 g of a 20 mass% Nafion (registered trademark) solution to obtain solution (A). Ultrapure water was added to 0.593 g of cerium (III) nitrate hexahydrate to obtain a total mass of 50 g of solution (B). Furthermore, ultrapure water was added to 0.280 g of iron (II) nitrate heptahydrate (radical generator) to obtain a total mass of 100 g of solution (C).

[0053] To solution (A), 1.00 g of solution (B), 0.94 g of solution (C), and 0.019 g of WO3 were added, and the mixture was irradiated with ultrasonic waves to obtain a dispersion in which tungsten oxide was dispersed. The obtained dispersion was cast into a petri dish, and the solvent was allowed to dry naturally. Next, the petri dish was annealed at 140°C for 15 minutes. After annealing, the membrane was washed five times with ultrapure water. Next, the membrane was peeled off from the petri dish and allowed to dry naturally. Furthermore, the membrane was immersed in ultrapure water at 80°C for 20 hours, and then allowed to dry naturally. The thickness of the obtained composite membrane was about 30 μm.

[0054] [1.1.2. Examples 1 to 6] An electrolyte membrane was prepared in the same manner as in Example 7, except that cerium nitrate was not added to solution (B) and the type and / or amount of tungsten oxide added was changed.

[0055] [1.1.3. Comparative Example 1] An electrolyte membrane containing neither Ce ions nor tungsten oxide was prepared in the same manner as in Example 7, except that cerium nitrate was not added to solution (B) and tungsten oxide was not added to solution (A). [1.1.4. Comparative Example 2] An electrolyte membrane containing only Ce ions was prepared in the same manner as in Example 7, except that tungsten oxide was not added to the solution (A).

[0056] Table 1 shows the average compositions of the films obtained in Examples 1 to 7 and Comparative Examples 1 and 2. In Examples 1 to 7, most of the added tungsten oxide was unevenly distributed on the petri dish surface side, so the average composition of tungsten oxide shown in Table 1 corresponds roughly to the average composition of tungsten oxide in the anode side region. [Table 1]

[0057] [1.2. Preparation of MEA] [1.2.1. Examples 1 to 7, Comparative Examples 1 to 2] The resulting composite membrane was cut into a 2.5 cm square. A catalyst layer was placed on both sides of the composite membrane, and the membrane was heated at 140°C for 5 minutes with 50 kgf / cm 2 These were transferred to a composite membrane by pressing under a pressure of 4.9 MPa to obtain an MEA. The catalyst layer attached to the cast surface (the surface facing the petri dish) during the casting process was used as the anode catalyst layer, and the catalyst layer attached to the surface facing the air was used as the cathode catalyst layer.

[0058] [1.2.2. Comparative Examples 3 to 4] An MEA was produced in the same manner as in Example 2. However, the catalyst layer bonded to the cast surface side was used as the cathode catalyst layer (Comparative Example 3). Moreover, an MEA was produced in the same manner as in Example 5. However, the catalyst layer bonded to the cast surface side was used as the cathode catalyst layer (Comparative Example 4).

[0059] 2. Test Method [2.1. Scanning electron microscope (SEM) observation] The obtained film was observed by SEM.

[0060] [2.2. Open circuit (OC) voltage endurance test] Gas diffusion layers were placed on both sides of the obtained MEA, and the MEA was assembled into a fuel cell. The electrode area was 0.64 cm 2 Next, the obtained fuel cell was subjected to an open circuit (OC) voltage durability test for 90 hours under the following conditions. Cell temperature: 95℃ Humidity: 30% RH for both anode and cathode Gas flow rate: 300cc / min (anode gas: H2, cathode gas: air) Back pressure: 133kPa

[0061] The humidified gas discharged from the fuel cell during the test was condensed, and the resulting water was collected every 24 hours. The collected water contained dissolved F ions that had been chemically decomposed from the electrolyte membrane. These were quantified using ion chromatography, and the cumulative amount of F ions up to 90 hours was calculated.

[0062] [2.3. IV performance] Using the obtained fuel cell, the IV performance was evaluated under the following conditions. Cell temperature: 95℃ Humidity: 40% RH for both anode and cathode Anode gas flow rate: H2, 500cc / min Cathode gas flow rate: Air, 2000cc / min Back pressure: 50kPa

[0063] [3. Results] [3.1. SEM Observation] Figure 1(A) shows an SEM image of the petri dish side surface of the electrolyte membrane obtained in Example 5. Figure 1(B) shows an SEM image of the air side surface of the electrolyte membrane obtained in Example 5. It was found that most of the added WO3 fine particles were present on the cast surface, and the fine particle content had a gradient in the membrane thickness direction.

[0064] [3.2. OC voltage endurance test] Fig. 2 shows the cumulative amount of F ion elution after 90 hours for the electrolyte membranes obtained in Examples 1 to 7 and Comparative Examples 1 and 2. The following can be seen from Fig. 2. (1) Comparative Example 1 is a membrane to which only Fe ions were added, and the amount of F ions eluted was the largest. (2) Comparative Example 2 is a membrane to which Fe ions and Ce ions were added. It was found that the amount of F ions eluted in Comparative Example 2 was reduced compared to Comparative Example 1, and deterioration was suppressed. This is believed to be because hydroxyl radicals generated by the reaction of H2O2 and Fe ions were quenched by Ce ions.

[0065] (3) Examples 1 to 3 are composite membranes to which WO2 has been added, and Examples 4 to 6 are composite membranes to which WO3 has been added. In Examples 1 to 6, the amount of F ion elution was also reduced compared to Comparative Example 1. This is believed to be because the generated H2O2 was decomposed by tungsten oxide. (4) Example 7 is a composite membrane to which Ce ions and WO3 were added. In Example 7, the amount of F ion elution was reduced compared to Comparative Example 2, and the effect of the combined addition of Ce and W was observed.

[0066] Figure 3 shows the cumulative amount of F ion elution after 90 hours for the electrolyte membranes obtained in Examples 2 and 5 and Comparative Examples 3 and 4. Example 2 is an MEA in which WO2 is unevenly distributed on the anode side, whereas Comparative Example 3 is an MEA in which WO2 is unevenly distributed on the cathode side. From Figure 3, it can be seen that Example 2 has a smaller amount of F ion elution than Comparative Example 3. Similarly, Example 5 is an MEA in which WO3 is unevenly distributed on the anode side, whereas Comparative Example 4 is an MEA in which WO3 is unevenly distributed on the cathode side. From FIG. 3, it can be seen that Example 5 has a smaller amount of F ion elution than Comparative Example 4. These results show that the deterioration of the electrolyte membrane can be suppressed by placing a large amount of tungsten oxide microparticles on the anode side.

[0067] [3.3. IV performance] FIG. 4 shows the IV performance of the fuel cells obtained in Example 2 and Comparative Example 2. In both Example 2 and Comparative Example 2, the amount of F ion elution after a 90-hour OC voltage endurance test was almost the same. However, the IV performance of Example 2 was higher than that of Comparative Example 2. This is believed to be because some of the protons of the acid groups of the electrolyte membrane of Comparative Example 2 were replaced with Ce ions, resulting in a decrease in the proton conductivity of the electrolyte membrane.

[0068] (Examples 8 to 14, Comparative Example 5) [1. Test method] 0.067 mmol of each additive was dispersed in 10 mL of water to prepare a dispersion, and 4.41 mmol of hydrogen peroxide was added to the dispersion. The additives used are shown in Table 2.

[0069] [Table 2]

[0070] The resulting dispersion was kept at 80° C. for 1 hour, and then the concentration of hydrogen peroxide remaining in the dispersion was measured. Furthermore, the hydrogen peroxide decomposition rate was calculated from the following formula (2). Hydrogen peroxide decomposition rate (%) = (C0-C) x 100 / C0…(2) however, C0 is the concentration of hydrogen peroxide in the original dispersion, C is the concentration of hydrogen peroxide in the dispersion after holding at 80°C for 1 hour.

[0071] [2. Results] Figure 5 shows the H2O2 decomposition rate for various additives. Figure 5 also shows the H2O2 decomposition rate when no additive was added (Comparative Example 5). It was found that under these experimental conditions, H2O2 did not self-decompose due to heat (Comparative Example 5). On the other hand, H2O2 decomposed not only when WO2 in Example 14 was used, but also when various tungstates in Examples 8 to 13 were used. From the above, it is expected that chemical degradation can be suppressed by combining tungstate with an electrolyte and placing a large amount of it on the anode side.

[0072] Although the embodiment of the present invention has been described in detail above, the present invention is not limited to the above embodiment, and various modifications are possible without departing from the gist of the present invention. [Industrial Applicability]

[0073] The membrane electrode assembly according to the present invention can be used in various electrochemical devices such as solid polymer fuel cells and solid polymer water electrolysis devices.

Claims

1. A membrane electrode assembly having the following configuration. (1) The membrane electrode assembly is an electrolyte membrane including a solid polymer electrolyte; an anode catalyst layer bonded to one surface of the electrolyte membrane; a cathode catalyst layer bonded to the other surface of the electrolyte membrane; First fine particles segregated on the anode side in the electrolyte membrane; Equipped with The first fine particles are made of a first compound having a function of decomposing hydrogen peroxide. (2) The solid polymer electrolyte includes a fluorine-based electrolyte and does not include a hydrocarbon-based electrolyte. (3) The first compound comprises WO 2 and / or WO 3 . (4) The average content of the first fine particles contained in a region (anode side region) from the surface on the anode side of the electrolyte membrane to the center of the electrolyte membrane is 1.0 mass% or more and 3.0 mass% or less, The average content of the first fine particles contained in a region from the center of the electrolyte membrane to the cathode side surface of the electrolyte membrane (cathode side region) is less than 0.1 mass %.

2. (a) ions of a second metal element having a radical scavenging function, which are ion-exchanged with protons of the acid groups of the solid polymer electrolyte, and / or (b) second fine particles made of a second compound containing the second metal element, the second fine particles being dispersed in the electrolyte membrane; The membrane electrode assembly of claim 1 further comprising:

3. The membrane electrode assembly according to claim 2 , wherein the second metal element is Ce.

4. The membrane / electrode assembly according to claim 2 or 3, which satisfies the following formula (1): 0.0005≦M / A≦0.15 (1) however, M / A is the ratio of the number of moles (M) of the second metal element to the number of moles (A) of the acid groups contained in the solid polymer electrolyte.

Citation Information

Patent Citations

  • Electrolyte membrane electrode assembly for solid polymer fuel cell and the solid polymer fuel cell

    JP2005093234A

  • Fuel cell

    JP2006244782A

  • Electrolyte membrane for fuel cell

    JP2007042491A

  • Solid polymer fuel cell

    JP2008159343A

  • Polymer electrolyte composition, and use application therefor

    JP2009211991A